Age Differences in Death and Suicidal Ideation in Anxious Primary Care Patients. Issue 4 (8th August 2018) - Petkus, Andrew J.; Wetherell, Julie Loebach; Stein, Murray B.; Chavira, Denise A.; Craske, Michelle G.; Sherbourne, Cathy; Sullivan, Greer; Bystritsky, Alexander; Roy-Byrne, Peter
ABSTRACT: Objectives : The objective of this study was to examine age differences in the likelihood of endorsing of death and suicidal ideation in primary care patients with anxiety disorders. Method : Participants were drawn from the Coordinated Anxiety Learning and Management (CALM) Study, an effectiveness trial for primary care patients with panic disorder (PD), generalized anxiety disorder (GAD), post-traumatic stress disorder (PTSD), and/or social anxiety disorder (SAD). Results : Approximately one third of older adults with anxiety disorders reported feeling like they were better off dead. Older adults with PD and SAD were more likely to endorse suicidal ideation lasting at least more than half the prior week compared with younger adults with these disorders. Older adults with SAD endorsed higher rates of suicidal ideation compared with older adults with other anxiety disorders. Multivariate analyses revealed the importance of physical health, social support, and comorbid MDD in this association. Conclusions : Suicidal ideation is common in anxious, older, primary care patients and is particularly prevalent in socially anxious older adults. Findings speak to the importance of physical health, social functioning, and MDD in this association. Clinical Implications : When working with anxious older adults it is important to conduct a thorough suicide risk assessment and teach skills to cope with death and suicidal ideation-related thoughts.